1997
DOI: 10.2307/1143954
|View full text |Cite
|
Sign up to set email alerts
|

"Driving while Black" and All Other Traffic Offenses: The Supreme Court and Pretextual Traffic Stops

Abstract: 2 See infra notes 15 through 19 and accompanying text. To legally stop a person, a police officer must have at least reasonable suspicion of criminal activity. Terry v. Ohio, 392 U.S. 1 (1968). S Brief for the United States at 5-6, United States v. Whren, 116 S. Ct. 1769 (1996) (No. 95-5841). 4 Whren, 116 S. Ct. at 1773 (defendant petitioners asked that the standard be "whether a police officer, acting reasonably, would have made the stop for the reason given" (emphasis added)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 0 publications
3
105
0
Order By: Relevance
“…The reason is likely because not long after the Eddie Bauer incident, racial profiling related to traffic stops caught the attention of legal scholars (D. A. Harris, 1997Harris, , 1999Harris, , 2002Russell, 1999Russell, , 2001, criminologists (Ramirez, McDevitt, & Farrell, 2000;Smith & Alpert, 2002;Weitzer & Tuch, 2002), as well as policymakers and funding agencies-which, in essence, doomed any significant interest in what was occurring in retail establishments. The significance of the problem in retail settings was further overshadowed by the terrorist attacks on 9/11 that produced an emphasis on profiling people of Middle Eastern descent (Onwudiwe, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The reason is likely because not long after the Eddie Bauer incident, racial profiling related to traffic stops caught the attention of legal scholars (D. A. Harris, 1997Harris, , 1999Harris, , 2002Russell, 1999Russell, , 2001, criminologists (Ramirez, McDevitt, & Farrell, 2000;Smith & Alpert, 2002;Weitzer & Tuch, 2002), as well as policymakers and funding agencies-which, in essence, doomed any significant interest in what was occurring in retail establishments. The significance of the problem in retail settings was further overshadowed by the terrorist attacks on 9/11 that produced an emphasis on profiling people of Middle Eastern descent (Onwudiwe, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As the profiling controversy began to gain momentum in the late 1990s, research projects were initiated by a range of state and federal political entities (Cox, Pease, Miller, & Tyson, 2001;Ekstrand, 2000;Langan, Greenfeld, Smith, Durose, & Levin, 2001;Nixon, 2001Schmitt, Langan, & Durose, 2002;Texas Department of Public Safety, 2001;Verniero & Zoubek, 1999;Zingraff et al, 2000), municipal police organizations (Cordner, Williams, & Zuniga, 2000;Decker & Rojek, 2002;Gamble et al, 2002;Lansdowne, 2000;Schafer, Carter, Katz-Bannister, & Wells, forthcoming;Smith & Petrocelli, 2001;Spitzer, 1999), advocacy groups (Lamberth, 1996), academics (Barlow & Barlow, 2002;Engel, Calnon, & Bernard, 2002; 1997Hoover, 2001;Knowles, Persico, & Todd, 2001;Meehan & Ponder, 2002a, 2002bNorris, Fielding, Kemp, & Fielding, 1992;Petrocelli, Piquero, & Smith, 2003;Walker, 2001;Weitzer & Tuch, 2002) and private citizens (Davis, 2001). These projects used a wide range of methodologies, including legal analysis, anecdotal evidence, observational research, citizen surveys, self-reported data provided by officers, and the analysis of existing data.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from organizational influences on stop patterns, the field has recognized that different types of traffic stops may be more or less prone to police discretion (Harris, 1997). For example, some argue that speeding stops are less discretionary compared to stops associated with violations of other types of traffic code.…”
Section: Disaggregating Traffic Stopsmentioning
confidence: 99%
“…The empirical focus on traffic stops stems from the use of traffic code violations by police as pretext to stop and investigate citizens based upon generalized suspicion, the legality of which was upheld by the Supreme Court's Whren v. U.S. (1996) decision. As many have suggested (Birzer & Birzer, 2006;Fagan & Davies, 2001;Harris, 1997;Meehan & Ponder, 2002;Smith & Alpert, 2002), pretextual stops have become a primary tactic in the police arsenal to address crime and especially the drug trade. Social scientists have recognized for decades that police form suspicion based upon a set of cues that signal danger (Skolnick, 1966), represent typifications of citizens and suspects (Van Maanen, 1978), and that these reflect the prejudices evident in the public at large (Bittner, 1967).…”
Section: Racial Profiling and Pretextual Stopsmentioning
confidence: 99%